Response strategies of five common warm temperate plant species to insect defoliation - Ning Wang; Qiang Li; Pan Wu; Shijie Yi; Hongliang Ji; Xiao Liu; Tongli He (BMC Ecology and Evolution)
Abstract Under the background of global climate change, climate warming has led to an increase in insect herbivory, which significantly affects the growth, survival, and regeneration of forest plants in the warm temperate zone of China. Plants can adopt defense responses to adapt to insect defoliation. Therefore, field experiments were conducted on five common warm temperate species, Quercus acutissima, Quercus serrata, Quercus aliena, Quercus dentata, and Robinia pseudoacacia. We measured the leaf traits of healthy trees and insect defoliated trees, to explore the response strategies of common species in warm temperate zones to insect defoliation. Our results showed that native species stored more carbon in extreme environments for survival rather than growth, while the alien species R. pseudoacacia tended to adopt active resource acquisition strategies and were more inclined towards growth. The content of tannins and flavonoids in the alien species R. pseudoacacia did not significantly increase after leaf damage, while the content of secondary metabolites such as tannins, flavonoids, and total phenols in the native species Q. acutissima, Q. serrata, Q. aliena, Q. dentata increased significantly after leaf damage. This indicated that compared to alien species, native species invested more resources in defense, which might reduce resource allocation for growth. Thus, the native Quercus species have stronger resistance than the alien species R. pseudoacacia after insect defoliation.